2012
DOI: 10.4103/2152-7806.94287
|View full text |Cite
|
Sign up to set email alerts
|

Subdural hematoma of the posterior fossa due to posterior communicating artery aneurysm rupture

Abstract: Background:We describe an unusual presentation of a ruptured aneurysm of the posterior communicating artery with an acute subdural hematoma (SDH) located in the posterior fossa. We also reviewed the literature, focusing on the location of this intracranial hematoma.Case Description:An 83-year-old woman was admitted to our institution with recent sudden headache and dizziness. Magnetic resonance imaging showed a thin collection of blood in the subdural space adjacent to the clivus, along the wall of the posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…However, the commonly accepted mechanism involves a breach of the arachnoid membrane due to the rapid accumulation of blood under local stress conditions. This could then lead to adhesion of the arachnoid to the aneurysmal dome, thereby inducing a direct rupture of the aneurysm into the subdural space [8,9]. In our patient, because of her aneurysmal configuration, we believe that the posterior communicating artery aneurysm expanded more into the Fig.…”
Section: Discussionmentioning
confidence: 78%
“…However, the commonly accepted mechanism involves a breach of the arachnoid membrane due to the rapid accumulation of blood under local stress conditions. This could then lead to adhesion of the arachnoid to the aneurysmal dome, thereby inducing a direct rupture of the aneurysm into the subdural space [8,9]. In our patient, because of her aneurysmal configuration, we believe that the posterior communicating artery aneurysm expanded more into the Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Hemorrhage can spread through the diaphragm sella into the subdural space, constrained by the posterior arachnoid membrane of the prepontine cistern [ 1 , 23 ]; on the other hand, a defect in the dorsum can permit blood flow into the epidural space [ 24 ]. Rare cases of rcSDH have been associated with aneurysmal rupture [ 25 , 26 ]. Moreover, pressure changes (spontaneous intracranial hypotension [ 7 ] and posterior fossa decompressive craniectomy [ 27 ]), thrombocytopenia [ 28 ], and hemophilia [ 29 ] have been linked with rcSDH.…”
Section: Discussionmentioning
confidence: 99%
“…There is a slight sex predominance toward males (60%), and the average age in surgical series is 50 years. [6][7][8][9][10][11]15,16 Arita et al found that over a 5-year follow-up period, pituitary apoplexy developed in 9.5% of patients with known pituitary adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty percent of patients also experience various forms of ophthalmoplegia, including diminished visual acuity, visual field defects, or diplopia. [6][7][8][9][10][11][12][13][14] In our series, all patients reported experiencing headache, and all but 1 patient had ophthalmoplegia of some kind. The recommended management-either conservative medical treatment 19 or surgical decompression 4,19 -remains controversial depending on the presence of associated cranial nerve palsies and level of consciousness.…”
mentioning
confidence: 93%